2023
DOI: 10.3390/membranes13070642
|View full text |Cite
|
Sign up to set email alerts
|

Silicas with Polyoxyethylene Branches for Modification of Membranes Based on Microporous Block Copolymers

Abstract: We have synthesized cubic and linear polysiloxanes containing polyoxyethylene branches (ASiP-Cu) using tetraethoxysilane, polyoxyethylene glycol, and copper chloride as precursors; the products are stable to self-condensation. The effect of copper chloride content on the chemical structure of ASiP-Cu has been established. A special study was aimed at defining the modifying effect of ASiP-Cu on the sorption characteristics of membranes based on microporous, optically transparent block copolymers (OBCs). These O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 62 publications
1
2
0
Order By: Relevance
“…In this study, the OBC was used to prepare analytical test systems, 1-(2-Pyridylazo)-2-naphthol (PAN) was used as an organic chromophore, and water-soluble copper salt was used as an analyte. According to previous studies [42], when modifying OBC using ASiP-Cu, a significant increase in the sorption capacity of the microporous block copolymer was observed. It was also found that the sorption capacity of OBC was also influenced by the method of preparing modifiers and its content in the polymer.…”
Section: The Analytical Test Systems Obtained Using the Obcsupporting
confidence: 56%
See 2 more Smart Citations
“…In this study, the OBC was used to prepare analytical test systems, 1-(2-Pyridylazo)-2-naphthol (PAN) was used as an organic chromophore, and water-soluble copper salt was used as an analyte. According to previous studies [42], when modifying OBC using ASiP-Cu, a significant increase in the sorption capacity of the microporous block copolymer was observed. It was also found that the sorption capacity of OBC was also influenced by the method of preparing modifiers and its content in the polymer.…”
Section: The Analytical Test Systems Obtained Using the Obcsupporting
confidence: 56%
“…The reaction solution was stirred on a magnetic stirrer without heating. The procedure for the synthesis of Cu(II)-coordinated polyoxyethylene-substituted silicas is given in [42]. After the complete dissolution of the reagents in toluene, TDI (5.4 g) was introduced into the reaction solution.…”
Section: Procedures For the Block Copolymers As Test Systems Synthesismentioning
confidence: 99%
See 1 more Smart Citation